Evaluating Eye Fixation and Color Contrast Effects in the Measurement of Visual Lobe Sizes: Comment on Tsang, et al. (2013). Issue 3 (December 2014) - Hong, Seung-Kweon
The visual lobe refers to the useful field of view, functional visual field, or conspicuity area in single eye fixation, and the visual lobe size is determined by the conspicuity of target presented amongst background characters. This comment discusses a study by Tsang, Chan, and Yu (2013) that investigated the effect of color contrast on the visual lobe. First, this comment suggests a way to improve the precision of their method for measuring a visual lobe. Measuring positions of the participants' eyes during visual search with an eye tracker would allow checking the eyes' fixation on the center of the search field, improving the precision of visual lobe measurement. This comment also suggests a more optimal experimental design to investigate the effect of color contrast on visual lobe size. Tsang, et al. used colors for target and background that had similar contrast (i.e., differences in chromaticity) for the experiments. If the color-contrast ratio in each experiment condition had differed enough, the color contrast effect on the visual lobe could have been investigated more effectively.